Relative influence of predators, competitors and seascape heterogeneity on behaviour and abundance of coral reef mesopredators. Issue 12 (25th October 2021) - Lester, Emily K.; Langlois, Tim J.; McCormick, Mark I.; Simpson, Stephen D.; Bond, Todd; Meekan, Mark G.
Abstract : Determining influences of predation and competition on community dynamics is particularly challenging in coral reef systems where interspecific interactions between many predator and prey species play out in patchy landscapes. We used 1000 stereo‐baited remote underwater video deployments (stereo‐BRUVs) to assess the relative abundance and analysed the behaviour of two size classes of mesopredatory teleosts (lutajnids, serranids, lethrinids) in the presence and absence of larger predators (mesopredatory and apex carcharhinids). For mesopredatory teleosts, the presence of sharks did not influence the abundance, time of arrival in vicinity of the stereo‐BRUVs, the probability of feeding on bait or the delay to feeding. Instead, the number of similar‐sized competitors and surrounding habitat features were the strongest drivers of these behavioural metrics. We suggest that for most fishes, the predatory threat posed by highly mobile species such as sharks is likely to be sporadic and transitory, whereas competition is ubiquitous and ever present, particularly for schooling taxa. Ultimately, it is likely that both processes interact to determine behavioural phenotypes as individuals that are inferior competitors can be displaced from safe habitats or prohibited from access to resources and will be more susceptible to predation. Future studies should consider the relative effects of both processes and the degree to which each can be shaped by habitat when investigating trophic dynamics that regulate marine communities.